2016
DOI: 10.1051/ijmqe/2016004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic calibration of piezoelectric transducers for ballistic high-pressure measurement

Abstract: Abstract. The development of a dynamic calibration standard for high-amplitude pressure piezoelectric transducers implies the implementation of a system which can provide reference pressure values with known characteristics and uncertainty. The reference pressure must be issued by a sensor, as a part of a measuring chain, with a guaranteed traceability to an international standard. However, this operation has not been completely addressed yet until today and is still calling further investigations. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Several principles have been used to construct devices for the non-destructive generation of strong pressure pulses, i.e., stronger than can in general be reached by shock tubes [14,15]. They include, for example, fast opening valves [7], the use of a commercial drop-weight apparatus [16], a dropweight apparatus designed for secondary calibrations using two piezoelectric sensors [8,17], a drop-weight apparatus measuring pressure via the monitoring of the deceleration of the piston [9,18,19], an air gun [16], a pressure-tank setup [10], or optical absorption spectroscopy [11]. Diamond anvil cells [20], well known for the very high pressures they can exert on small samples, necessarily need to be smallvolume devices, too small to permit attaching a customer's transducer (typical sensor casings use M10 or M12 threads).…”
Section: Introductionmentioning
confidence: 99%
“…Several principles have been used to construct devices for the non-destructive generation of strong pressure pulses, i.e., stronger than can in general be reached by shock tubes [14,15]. They include, for example, fast opening valves [7], the use of a commercial drop-weight apparatus [16], a dropweight apparatus designed for secondary calibrations using two piezoelectric sensors [8,17], a drop-weight apparatus measuring pressure via the monitoring of the deceleration of the piston [9,18,19], an air gun [16], a pressure-tank setup [10], or optical absorption spectroscopy [11]. Diamond anvil cells [20], well known for the very high pressures they can exert on small samples, necessarily need to be smallvolume devices, too small to permit attaching a customer's transducer (typical sensor casings use M10 or M12 threads).…”
Section: Introductionmentioning
confidence: 99%
“…One such application is the measurement of pressure within automotive engine cylinders to improve understanding of the combustion process, enabling engine efficiency optimisation (Wang et al, 2015). At present, the calibration of such pressure measurement systems is performed against static pressure standards, as dynamic pressure standards of both the required amplitude and frequency content are not readily available, although work is underway at various laboratories around the world to remedy this situation (Elkarous et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The different types of equipment used for dynamic calibration of pressure sensors are discussed with principles and limitations (Theodoro et al, 2018;Zafer et al, 2017;Damion, 1994). Elkarous et al (2016) have demonstrated the calibration setup using hydraulic pressure pulse generator to evaluate dynamic parameters of ballistic pressure transducers. The dynamic pressure calibrator using the microphone as a reference standard is demonstrated by Feero et al (2018).…”
Section: Introductionmentioning
confidence: 99%